(untitled) (Veterinary Science, 2025)
The objective of this study was to evaluate the aboveground biomass production and nutritional quality of native and introduced summer forage species used in the semiarid Pampas region for improving forage supply and restoring degraded grasslands. The native summer grasses evaluated were two populations of Leptochloa crinita and one of Pappophorum caespitosum. The introduced grasses were: Eragrostis curvula, Panicum coloratum, Eragrostis superba, Tetrachne dregei, and Digitaria eriantha. The experimental design followed a completely randomized block design with three replicates, using 1.5 m² plots per species, each containing 12 plants spaced 50 cm apart. Differences between treatments were assessed using ANOVA, followed by Tukey’s test for mean comparison (p<0.05). Biomass and nutritional quality were assessed in autumn and spring. Introduced species showed higher biomass production during both seasons (autumn and spring) in the first year. Similarly, forage quality was higher in the introduced species, with P. coloratum standing out in particular. Native species, P. caespitosum and L. crinita, generally had higher fiber content and lower digestibility, although their protein content was high in spring. Understanding the biomass production and quality of native species compared to introduced ones is crucial for making informed decisions regarding the selection and use of forage resources in the central semiarid region of Argentina.